The development of a Microtakaful model to serve the underprivileged: low income and the poor in selected states in Malaysia / Noor Ashikin Mohd Rom - Mohd Rom, Noor Ashikin (Institute of Graduate Studies, UiTM, 2015)
Microtakaful is one of the mechanisms to alleviate the poverty and to provide necessary protection to low income and the poor. The purpose of this research is to investigate the need for protection (microtakaful) among low income and the poor respondents and finally to develop a suitable microtakaful model based on the findings of the survey, theories and literature reviews. Firstly, need for protection was examined by investigating respondents’ demographic profile, their exposure to risks, vulnerability (coping strategies), their financial literacy (ability to save and indebtedness), the awareness level, their capacity to contribute, attitude and trust towards takaful or insurance. Secondly, a new variable namely capacity to contribute was established to investigate the statistical relationship with the need for protection. Thirdly, this study employed income and education level as moderators to moderate vulnerabilities and need for protection. The objective is to find the moderation effect of income and education level on vulnerabilities and need for protection. Another new moderator namely government role is employed to test the relationship between capacity to contribute and need for protection. Fourth, this study also investigates respondents’ protection and contribution method preferences, mode of contribution and finally an affordable amount that they are willing to part with on a monthly basis. Need for protection would reflect the potential demand for these population; low income and poor…